Contribution Power of Arm and Eye-Hand Coordination to Ability Throw Softball of Universitas Islam Riau (Department of Physical Education, Sport, Health and Recreation, 2019)
This study aims to determine the ability of a student throws a softball game physical education student of Universitas Islam Riau 2016/2017. Data collection methods used in this research is to use the test and measurement techniques. The test instrument in this study using a bicep strength test (push-ups), eye-hand coordination test and a test throws. The population in this study were physical education students of Universitas Islam Riau 2016/2017 forces who took a course softball. While samples taken in this study are all students. The sampling technique in this study using total sampling technique. Data analysis methods used were descriptive statistics, statistics is aimed at collecting data, presenting data and determine the value. Further data were understanding as our discussion of the issues addressed by the standard refers to the ability tosses in a softball game. Based on the results of research and discussion, it can be concluded as follows: there is a link arm muscle strength and hand-eye coordination to the results of throw inter-base student courses softball physical education students of Universitas Islam Riau 2016/2017 amounted to 12.46% with the count r = 0.353 and r 0.220 table while the excess of 87.54% influenced by other factors.